Pengaruh Suasana Toko terhadap Citra Toko di Hypermart Pondok Gede - Desi Intan Arisanti; Nur Busyra (Jurnal Utilitas, 2016)
This study aimed to determine the effect of store atmosphere to store image at Hypermart Plaza Pondok Gede. The population of this study is all Hypermart customers who visited Plaza Pondok Gede during the study period. The sample of this study amounted to 50 customers who taken uses incidental sampling technique. This research uses associative quantitative research method. After the data have the same characteristics and normal distribution based on normality and homogeneity test, followed by analysis of variance (ANAVA). Based on the results of linear regression calculations obtained ŷ = 64,93 + 0,36 (x) and the calculation of ANAVA obtained Fhitung < Ftabel (0.79 , 1.96). Hypothesis testing is done by calculating the correlation of pearson product moment and obtained rxy = 0.362, it shows the influence of storeatmosphere to store image at Hypermart Plaza Pondok Gede is Low in accordance with the interpretation criteria in Table Interpretation of Correlation Coefficients. Therefore, the results of this study can be concluded that there is influence between store atmospher to store image at Hypermart Plaza Pondok Gede.